'Journey to the future': imaginaries and motivations for homeland trips among diasporic Armenians. (16th November 2016) - DARIEVA, TSYPYLMA
Abstract: This article highlights diasporic migrants' transnational linkages with and trips to their homeland. Second and later generations of diasporic Armenians, predominantly from the USA and Canada, claim to travel to the ancestral homeland in Armenia not as heritage tourists to see the holy Mount Ararat but to invest in local development through social work. Based on ethnographic research, in‐depth interviews with volunteers and text materials, this article identifies those specific features of the contemporary diasporic 'sacred journey' that differ from conventional return migrations. This new inter‐continental migratory path between North America and Armenia has a temporary character. By analysing the range of reasons why young professional Armenian‐Americans and Armenian‐Canadians should choose to travel the long distance to offer their services, this article provides insight into the decision to become a volunteer in Armenia and the ways non‐profit diasporic organizations channel and mobilize this transnational activity. The study shows that 'ethnic' volunteers are highly conscious of the modern understanding of mobility as being a marker of personal social status within the society in which they grew up. The study of a variety of imaginaries among members of a paradigmatic diasporic group, such as Armenians, shows how second and later diasporic generations take advantage of their multi‐cultural background to become transnational global actors.